Strategi Transformasional dalam Menerapkan Pemahaman yang Benar tentang Makna Ibadah menurut Mazmur 95:6-7 - Ayu Pratiwi Nehe; Irwan Putra Jaya Laia; Malik Bambangan (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
It is essential to have a correct understanding of the true meaning of worship, according to Psalm 95:6-7. The concept of worship in the book of Psalms is more related to the closeness of the people’s hearts to God than just rituals or outward ways. In this text, all people are invited to come with sincere respect and worship to God, as a recognition of His power and sovereignty. Understanding that worship is not just a task or routine is part of kuni in applying the correct understanding of the meaning of worship. In the book of Psalms, God is described as a shepherd who cares for His people. This shows that people perform worship in response to God’s love and providence. As a result, a transformational approach must involve a change of mind and heart. In the context of Psalm 95:6-7, the transformational strategy in question involves fostering the spiritual character of the people through in-depth teaching and the application of spiritual principles in daily life. This strategy includes understanding the importance of sincerity in worship, not just following established forms of worship. In this regard, spiritual leaders and church leaders have an important role in providing guidance, teaching the faithful to understand the meaning of true worship, and helping them avoid the bonds of worship formalities. In addition, transformational strategies in worship also include the participation of the faithful in social life that reflects values such as love, justice, and sacrifice, which are at the core of worship itself.